1987
DOI: 10.1111/j.1365-2915.1987.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Honeydew sugars in wild‐caught Phlebotomus ariasi detected by high performance liquid chromatography (HPLC) and gas chromatography (GC)

Abstract: Phlebotomus ariasi Tonnoir sandflies were caught in light traps hung in oak trees and in a house in the Cévennes focus of leishmaniasis in the South of France. The flies were cryopreserved either immediately on removal from the traps, or after starvation for 6-7 days, or after 6-7 days starvation followed by exposure to oak infested with the aphid genera Lachnus or Thelaxes. After transportation to the laboratory, the sandflies were thawed and aqueous extracts of the crushed flies were analysed for their carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
0
37
0
3
Order By: Relevance
“…1 Female sand flies require blood to support the growth of eggs, and both sexes take ''sugar meals'' consisting of plant tissues or honeydews excreted by aphids and coccids to sustain their daily activities. [2][3][4][5][6] Observations in a typical arid focus of L. major in the Jordan Valley indicated that the sand flies obtained sugars by feeding only on a limited number of plant species. 7 Since the developmental cycle of Leishmania parasites in the sand fly is restricted to the gut, they are exposed to the ingested tissues of the various plants upon which the sand flies feed.…”
Section: Introductionmentioning
confidence: 99%
“…1 Female sand flies require blood to support the growth of eggs, and both sexes take ''sugar meals'' consisting of plant tissues or honeydews excreted by aphids and coccids to sustain their daily activities. [2][3][4][5][6] Observations in a typical arid focus of L. major in the Jordan Valley indicated that the sand flies obtained sugars by feeding only on a limited number of plant species. 7 Since the developmental cycle of Leishmania parasites in the sand fly is restricted to the gut, they are exposed to the ingested tissues of the various plants upon which the sand flies feed.…”
Section: Introductionmentioning
confidence: 99%
“…Since they rest outside, they cannot be efficiently controlled using inside residual spraying with insecticides [12,16]. Both male and female sand flies have sugar feeding from natural sources such as juices of plants [22] and honeydews of aphids [23][24][25][26]. The females have also blood feeding because they need the blood to produce the nutrition required for their egg production.…”
Section: Sand Fly Vector Biologymentioning
confidence: 99%
“…En términos de alimentación de los adultos, también hay una gran variedad de fuentes naturales de azúcar, que incluyen el fruto maduro del café y el guamo, lo que facilita el establecimiento de los parásitos del género Leishmania en los insectos vectores (39,52,53). Asimismo, las fuentes de ingestión sanguínea de los flebotomíneos pueden incluir roedores silvestres (Micoureus demerarae y Microryzomys minutus) y otros mamíferos, así como los animales domésticos y los residentes humanos que viven cerca o entre los cultivos del café (54,55).…”
Section: Leishmaniasis Y Flebotomíneos En Ecosistemas De Influencia Cunclassified
“…Además, en lo concerniente a los nuevos registros, se detalla el método de recolección utilizado. Los resultados de la presente revisión confirman que la zona cafetera del país es, en efecto, un área de riesgo potencial, donde la presencia de especies vectores se suma a la evidencia de transmisión activa de la enfermedad dentro o alrededor de las casas o cerca a las plantaciones de café, lo que tiene un impacto directo sobre las poblaciones humanas que viven y trabajan en dichas plantaciones, por lo cual sería de suma importancia desarrollar actividades de vigilancia entomológica (39,40,41,(54)(55)(56)61,65,66,75 Entre los nuevos registros de especies cuya presencia se suma a la lista conocida de especies para la zona cafetera, sobresalen las siguientes: Brumptomyia sp. cerca a guimaraesi, Lu Las posibles nuevas especies y nuevos registros de especies para los departamentos de Antioquia, Caldas y Quindío, se presentan en el cuadro 2.…”
Section: Estructuración De La Listaunclassified
See 1 more Smart Citation